A novel C-type lectin with four CRDs is involved in the regulation of antimicrobial peptide gene expression in Hyriopsis cumingii. (August 2016) - Zhao, Ling-Ling; Wang, Yu-Qing; Dai, Yun-Jia; Zhao, Li-Juan; Qin, Qiwei; Lin, Li; Ren, Qian; Lan, Jiang-Feng
Abstract: C-type lectins (CTLs) are found in a wide number of invertebrates, and have been reported to participate in immune responses, such as the activation of prophenoloxidase, cell adhesion, bacterial clearance and phagocytosis. Previous studies on CTLs focused on the function of their carbohydrate recognition domains (CRDs). Currently, studies on lectins with multi-CRDs are limited. In this study, a lectin with four CRDs was cloned from Hyriopsis cumingii, and called HcLec4 . HcLec4 was widely distributed in several tissues and was significantly down-regulated at the early stage (2 h) of bacterial infection. We further analyzed the bacteria and carbohydrate binding activities of Hc Lec4. The results showed that Hc Lec4 could bind to several bacteria, lipopolysaccharide (LPS) and peptidoglycan (PGN). In HcLec4 knockdown mussels, the bacterial clearance rate was increased, and the expression level of antimicrobial peptides (AMPs) was up-regulated. This study reveals that HcLec4 exerts its antibacterial effect by regulating the expression of AMPs at the early stage of bacterial infection. Highlights: HcLec4 widely expressed in the several tissues. HcLec4 was downregulated under bacteria challenge. The bacteria clearance efficiency was increased after HcLec4 knockdown. The expression level of AMPs were upregulated after HcLec4 knockdown.